Analysis of Threshold Voltage Shift in AlGaN/GaN Heterostructure Field-Effect Transistors with Different Buffer Layers. Issue 8 (1st January 2015) - Liao, Wen-Chia; Chen, Cheng-Hsin; Hsu, Chia-Wei; Hsin, Yue-Ming; Chyi, Jen-Inn
Abstract : This study applied a methodology for defining the threshold voltage shift (ΔVTH ) transient of AlGaN/GaN heterostructure field-effect transistors (HFETs) to observe the influence of traps in AlGaN/GaN HFETs with different buffer layers: a carbon-doped (C-doped) buffer and an Al0.05 Ga0.95 N back barrier layer. This methodology involves synchronous switching of gate-to-source voltage (VGS ) and drain-to-source voltage (VDS ). Two HFETs demonstrated similar transient behaviors but different trends by enduring various VDS stress level. For devices with a C-doped buffer layer, the amount of threshold voltage shift becomes saturated with increasing VDS stress; however, a device with an Al0.05 Ga0.95 N back barrier layer does not. A simulation tool was used to analyze the trap behaviors and close agreement was seen between measured and simulated.